Comparative N‐glycoproteomic analysis of Tibetan and lowland chicken fertilized eggs: Implications on proteins biofunction and species evolution. Issue 1 (3rd December 2021) - Meng, Yaqi; Chen, Diao; Qiu, Ning; Mine, Yoshinori; Keast, Russell; Meng, Sichong; Zhu, Chunxia
Abstract: The characterization and functionality of protein glycosylation among different related species are of common interest. Herein, non‐standard quantification and N ‐glycosylation enrichment technology combined with ultra‐high liquid chromatography‐tandem mass spectrometry were used to establish detailed N ‐glycoproteomics of fertilized eggs, and quantitatively compared between Tibetan and lowland chicken. A total of 396N‐glycosites from 143 glycoproteins were found. Specifically, compared with lowland chicken egg white, 32N‐glycosites of 22 glycoproteins were up‐regulated and 57N‐glycosites of 25 glycoproteins were down‐regulated in Tibetan chicken egg white. Also, 137N‐glycosites in 72 glycoproteins showed much higher‐degree glycosylation and 36N‐glycosites in 15 glycoproteins displayed lower‐degree glycosylation in Tibetan chicken egg yolk than those in lowland chicken egg yolk. Through bioinformatic analysis, these varied glycoproteins were highly associated with antifreeze activity, hypoxia adaptation, coagulation cascade, and binding/immunity activities, which may be related to plateau hypoxia and cold stress. Practical applications: These findings provide a new insight on the role of biological egg N ‐glycoproteins related to environmental adaptation and evolution, which may be further applied in improving egg processing and human health, by developing biomolecules for food and medical industry. Abstract : Workflow of the N‐glycoproteomic analysis egg white and egg yolk from Tibetan and lowland chickens.